Systematic review of collateral effects of focused interventions for children with autism spectrum disorder. (November 2017) - Ledbetter-Cho, Katherine; Lang, Russell; Watkins, Laci; O'Reilly, Mark; Zamora, Claudia
A collateral intervention effect refers to changes in behaviors which were not directly targeted during intervention. Using predetermined search and inclusion procedures, this systematic review identified 46 studies involving children with autism spectrum disorder and 14 desirable collateral effects across multiple domains of functioning. Collateral effects were associated with: (a) interventions involving naturalistic behavioral strategies; (b) participants with limited communication and/or cognitive deficits; (c) performance deficits (i.e. there was some evidence of the collateral behavior in baseline); and (d) interventions directly targeting play, communication, joint attention, and/or stereotypy. Overall, this systematic review indicates that collateral effects arising from focused interventions warrant consideration by practitioners during intervention planning and require additional research to identify mechanisms responsible for the observed changes.